Gestão escolar e os processos de inclusão na escola comum : um estudo comparado internacional - Godoy, Ellis Regina dos Santos (2018)
The objective of this study was to analyze aspects of the work of the school director that considers the inclusive perspective of public-targeted students of Special Education enrolled in common schools located in the municipalities of Vitória-BR and Xalapa-MEX. Considering the debate about school management theories (PARO, 2010, LUCK, 2012, LIBÂNEO, 2013), it was necessary to discuss the ways of working of the school director and the developments of this practice for Special Education. This research was delineated as a international comparative study, which focused on the school management work developed in common schools located in Vitória-BR and Xalapa-MEX. The research involved three Mexican schools and two Brazilian schools. Data collection in both realities was carried out in 2017, and in Mexico it occurred during a mission of international studies. In this context, we resorted to the analysis and discussion of the role of the school director in the process of inclusion of students with disabilities in these two realities. As a theoretical contribution, the concepts of Norbert Elias (1993, 1994, 2006) help to think of society and individual as inseparable entities. In this conception, the director's work permeates social relations and the multiple figurations of which he is a part. The data point out the need to overcome the fragmentation of tasks in the daily school life, which considers the role of the director in a hierarchical way and separated from the pedagogical context of his performance, avoiding the model of the New Public Management. In addition, it is also a question of rethinking the processes of teacher training to work with the target audience of Special Education in order to foster inclusive practices in this context, suggesting the participation of all professionals in the inclusion process. Considering the systematized data and using the theoretical reference of Norbert Elias, it can be observed that the school director is not alone in this context, because its practice depends to a great extent on the many actions of the different individuals that compose this space.